Oral Glutamine Supplement Inhibits Ascites Formation in Peritoneal Carcinomatosis Mouse Model. (30th September 2013) - Chen, Ming-Jen; Wang, Tsang-En; Tsai, Shu-Jung; Lin, Ching-Chung; Liu, Chia-Yuan; Wang, Horng-Yuan; Shih, Shou-Chuan; Chen, Yu-Jen
Abstract : Background . Peritoneal carcinomatosis (PC) accompanied with ascites formation causes several distressing symptoms, resulting in poor quality of life. Methods . Twenty BALB/c nude mice generated by direct orthotopic injection of human pancreatic cancer PANC-1 cells were randomized to receive either a stock laboratory diet or a stock diet supplemented with glutamine. Half of the mice were sacrificed at day 76 to measure the amount of ascitic fluid and pancreatic tumor volume. The remaining mice were subject to survival analysis. Serum albumin levels were estimated every 2 weeks. Results . At day 76, the average amount of ascitic fluid measured in the control group was 1.2 ± 0.3 mL compared to 0.5 ± 0.5 mL from the glutamine-supplemented mice (P = 0.045 ). The volume of pancreatic tumor was 2.60 ± 0.8 cm 3 in the control group and 1.98 ± 1.3 cm 3 in glutamine-supplemented mice (P = 0.39 ). The mean survival time of glutamine-supplemented mice was prolonged from 87 ± 4 to 101 ± 2 days (P = 0.0024 ). Mean serum albumin levels were higher in the glutamine-supplemented group. Conclusions . This preclinical study showed that oral supplementation of glutamine may provide ascites-reducing activity in pancreatic cancer patients with PC, via a cell-mediated immunity-independent mechanism.